+0  
 
0
61
1
avatar

If the roots of the equation 3x^2 - 6x + 5 = 0 are a and b, then find the quadratic whose roots are a + b and 2/(a + b).

 Feb 20, 2021
 #1
avatar+118069 
+1

By Vieta

 

To avoid confusion......let  m  and  n  be  the roots

 

The  form is    ax^2  + bx  +  c     where  a  = , b = -6    

 

Sum of  the  roots  = m  + n  = -b/a  =  - ( - 6 ) / 3   =   2

 

So......in our new quadratic....let  a  =  1

 

(m + n)  +  2 / ( m + n)    =     2  +  2 / 2   =   2  + 1    =    3   =  -b    →  -3   =  b

 

And  the  product  of  the roots = c  =   (m + n)  * 2  / (m + n ) =   2

 

The quadratic  is   ax^2 + bx  + c   =       x^2   -  3 x  +  2

 

 

cool cool cool

 Feb 20, 2021

10 Online Users